Strategi pengembangan desa wisata osing dalam upaya pemulihan ekonomi pada masa pandemi Covid-19 - Adhinda Dewi Agustine; Akbar Pandu Dwinugraha (Universitas Merdeka Malang, 2021)
This study tries to find a strategy for developing the Osing Tourism Village as an effort to recover the economy during the Covid-19 pandemic. This type of research is a combination (mix method) used in this study. The research location is Osing Tourism Village in Banyuwangi Regency with the target group being a tourism-aware group that manages Osing Tourism Village. The time for collecting research data is in the period June - September 2021. Based on the results of the data obtained, four strategies are produced that can be used for the development of the Osing tourism village. First, optimizing the improvement of the image and branding of the Osing Indigenous Tourism Village so that it remains the choice of tourist destination in the New Normal era. Second, increasing the capacity of human resources for tourism actors in the use of digital technology facilities to support tourism during the Covid-19 pandemic. Third, changing the trend of tourism into technology-based tourism in terms of product marketing and tourism management. To bring the Osing tourism village to life through product innovations that are preferred by consumers with attractive and contemporary packaging models. Fourth, collaborate with the private sector and local governments in providing facilities and infrastructure to support tourism activities during the Covid-19 pandemic.